The effect of social support on improving athlete performance: a bibliometric trend analysis - Ferry Fendrian; Faiz Adji Musfika; Indra Sholehudin (MEDIKORA, 2026)
This study aims to conduct an in-depth bibliometric analysis of the evolution of scientific publication trends regarding the impact of social support on athlete performance. Unlike previous studies that were often partial to specific sports or age groups, this research examines literature holistically from the Scopus database without demographic specification limitations to obtain a comprehensive global overview. Using VOSviewer software, this study maps publication patterns, influential authors, top journals, and the intellectual structure linking social support with mental resilience and athlete achievement. The results show a significant surge in publications over the last decade, with the United States, the United Kingdom, and Australia as dominant contributing countries. Key findings identify that social support functions as a crucial multidimensional mechanism for athletes' emotional stability across various competitive levels. This study provides strategic insights for coaches and sports practitioners to integrate psychosocial interventions into team management and recommends future researchers expand data coverage beyond Scopus to bridge existing literature gaps.